From Middle-Age to the Golden Years: Medical, Surgical and Rehabilitation Considerations to Maintain Exercise and Sports Activities with Knee Osteoarthritis - Nyland, John; Sirignano, Michael; Krupp, Ryan (TERRA ORTHOPAEDICA, 2024)
Abstract. The objective of the current concepts paper is increase the reader’s awareness and understanding of medical, surgical, and rehabilitation considerations for middle-aged patients with knee osteoarthritis who desire to preserve knee joint function and quality of life as they continue exercise and sport activities into their “golden years”.